Custodias de sol del siglo XVII en la antigua diócesis de León - Alonso Benito, Javier (Estudios humanísticos. Geografía, historia y arte, 1998)
Around the year 1600 a series of important changes in Spanish art took place, aesthetic and morfologicals changes which would be promoted through diferent artistics disciplines. The silver work would not be an exception taking part in such a way as to create a new tipe of piece whose evolution throughout the seventeen century would favour its consolidation in the years to folow. We are talking about the "Custodia de Sol", a model which meant an step forward in the craftsmanship of religious art.